THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB), ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE OF PT. TASPEN BRANCH LHOKSEUMAWE CITY - Muhammad Ghazali Alwafi Lubis; Likdanawati; Khairawati; Sullaida; Nurmala (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Good human resource management is the key to the success of an organization in achieving its goals. At PT. Taspen Branch of Lhokseumawe City, it was found that there were challenges in efforts to improve employee performance. Some employees showed a decrease in productivity even though they were in a stable position. Based on temporary observations, it can be concluded that the low performance of employees at PT. Taspen Branch of Lhokseumawe City was influenced by the ineffectiveness of transformational leadership, low recognition of Organizational Citizenship Behavior (OCB), and weakening organizational commitment. The purpose of this study was to see the effect of transformational leadership, Organizational Citizenship Behavior (OCB), and organizational commitment on employee performance at PT. Taspen Branch of Lhokseumawe City. This type of research uses a quantitative method, data collection using a questionnaire containing questions and statements by distributing it to the employees concerned at PT. Taspen Branch of Lhokseumawe City. The scoring technique uses a Likert scale. This research was conducted at PT. Taspen Branch of Lhokseumawe City with a total of 62 respondents, where the sampling in this study used saturated samples, where all populations were sampled so that the number of samples in this study was 62 respondents. This study used multiple linear regression analysis with the SPSS (Statistical Program for Social Science) program. The results of this study indicate that transformational leadership, Organizational Citizenship Behavior (OCB), and organizational commitment have a positive and significant influence on employee performance at PT Taspen Branch of Lhokseumawe City. This shows that the transformational leadership style applied by superiors, good implementation of OCB, and strong and positive organizational commitment contribute significantly to improving employee performance.